Adverse Childhood Experiences (ACEs) in Specific Vulnerable Developmental Periods Can Increase the Likelihood of Chronic Pain in Adulthood—Results from a Cross-Sectional Study - David Riedl; Christina Kirchhoff; Ulrich T. Egle; Tobias Nolte; Michael Tschuggnall; Gerhard Rumpold; Wilhelm Kantner-Rumplmair; Vincent Grote; Michael J. Fischer; Astrid Lampe (Diagnostics)
Background: Adverse childhood experiences (ACEs) have been identified as a major risk factor for physical and mental ill health in adulthood. So far, no studies have investigated whether ACEs during sensitive periods in infant development are associated with a higher likelihood of chronic pain (CP) in adulthood. Methods: Patients of the University Hospital of Innsbruck (Austria) completed questionnaires retrospectively assessing their ACEs as well as their current levels of CP, psychological distress, and trauma-related symptoms in this cross-sectional study. Dose-dependent associations of ACEs with CP were investigated through binary logistic regressions. To detect vulnerable developmental periods, a machine learning grid search was applied. Results: A total of n = 2577 patients were included in the analyses, with 31.5% reporting CP. Polytraumatization (i.e., four or more types of ACEs) was associated with a threefold increase for CP (OR: 3.01; 95% CI: 2.16–4.19; p < 0.001). The machine learning approach revealed maltreatment between 10 and 12 years to be the most predictive of CP (Ada Boost Classifier). Discussion: CP is a highly prevalent symptom among hospital patients and is clearly associated with ACEs. This is the first study to present evidence for a timing-dependent association of ACEs with CP. Early identification and appropriate psychosocial support for patients with ACEs is a crucial task for healthcare professionals.